Understanding social networks and social support resources with sports coaches - Norris, L. A.; Didymus, F. F.; Kaiseler, M. (Psychology of Sport and Exercise, 2020)
Objectives: Research on social support with sports coaches is limited, yet the benefits of social support within other occupations have been widely reported. This study explored sports coaches` social network structures, the social support resources available to coaches, and the situations in which coaches use social support.